THE ROLE OF ROLE PLAYING METHODS ON THE IMPLEMENTATION OF RELIGIOUS AND MORAL VALUES BASED ON CARTOON/ANIMATION FILM BASED ON KARUN/ANIMATION FILM AGES 5-6 YEARS OLD - Nurhayati Nurhayati; Fitriana Fitriana; Patipurnama Patipurnama; Durrotunnisa Durrotunnisa (International Journal of Social Science, 2022)
This problem is the cultivation of children's religious and moral values ​​has not developed properly. In connection with this problem, the aim is to determine the role of the role-playing method in instilling religious and moral values ​​in children based on cartoon/animated films during the COVID-19 pandemic aged 5-6 years. The approach in this research is qualitative and the type of research is descriptive. The subjects were 24 children consisting of 11 boys and 13 girls. Data was collected by means of observation, interviews, and documentation. Data management is done by using percentage technique. Based on the results of the study showed that the first week of the average recapitulation results on aspects of good behavior, reading prayers and honesty, the category developed very well (****) 2.8% of children, the category developed as expected (***) 7% of children, the category began to develop (**) 19% of children, and underdeveloped category (*) 70.8% of children. Furthermore, after the fourth week using the role playing method and its media, namely cartoon/animated films from the recapitulation on aspects of good behavior, reading prayers, and honesty, the average category developed very well (****) 19.4% of children, the category developed according to expectations (***) 65.3% of children, the category began to develop (**) 11.1% of children, and the undeveloped category (*) 4.2% of children. It can be concluded that there is a role for the role-playing method to inculcate religious and moral values ​​in children based on cartoon/animated films.